Microbial biomass, fungal and bacterial residues, and their relationships to the soil organic matter C/N/P/S ratios - Khan, Khalid Saifullah; Mack, Ralf; Castillo, Xiomara; Kaiser, Michael; Joergensen, Rainer Georg (Geoderma, 2016)
The interrelations between the microbial biomass, total N, organic P, and organic S in the accumulation of soil organic C (SOC) and the contribution of fungal and bacterial residues to SOC, based on amino sugar data, were investigated in the current study. The soils had been developed under humid temperate, arid sub-tropical, and tropical climatic conditions and were used as arable, grass, and forest land. They covered a wide range in soil pH, in salinity as well as in the contents of clay and SOC. An increased microbial biomass C/N ratio due to nutrient limitation is not reflected by any increase in SOM elemental C/N/P/S ratio within the total nutrient pool or within the organic fraction. Increased SOC/total N and SOC/organic S ratios reduced the contribution of microbial biomass C to SOC, whereas neutral soil pH and high clay contents had positive effects. An increased formation of microbial biomass C also enlarged the contribution of microbial residue C to SOC, which accounted on average for 48% SOC in the neutral arable and moderate acidic grassland soils and for 30% in the saline arable and strongly acidic forest soils. The fungal C to bacterial C ratio increased with increasing acidity from 0.9 in the saline arable soils to 4.5 in the strongly acidic forest soils. Consequently, the relationship of the fungal C to bacterial C ratio was not simply related to the contribution of microbial residues to SOC. The lower the ergosterol to fungal GlcN ratio, the higher the contribution of microbial residues to SOC. This means the higher the contribution of arbuscular mycorrhizal fungi and the lower the contribution of saprotrophic fungi to the microbial community, the more fungal residues can be sequestered to SOC. •Median SOC/total N and SOC/organic P ratios were similar in agricultural soils.•Median SOC/organic S ratios were more variable, especially in saline arable soils.•All elemental ratios were roughly doubled in strongly acidic forest soils.•Microbial residues contributed roughly 50% to SOC in arable and grassland soils.•Microbial residues contributed only 30% to SOC in saline arable and forest soils.